Effect of different agrochemicals as foliar spray on the growth performance of mango grafts cv. Amrapali - Haque, Md Mazharul; Rahim, MA; Choudhury, MSH (Journal of Bio-Science, 2012)
No abstract available. DOI: http://dx.doi.org/10.3329/jbs.v19i0.13009 J. bio-sci. 19 101-103, 2011